2001
DOI: 10.4049/jimmunol.166.1.346
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Human Dendritic Cells Expresses IgA Fc Receptor (CD89), Which Mediates Internalization and Activation Upon Cross-Linking by IgA Complexes

Abstract: Immature dendritic cells (DC) sample Ags within nonlymphoid tissues and acquire exogenous proteins/pathogens via scavenger receptors or Ig FcR such as FcγR and FcεR. IgA is present in a significant proportion among serum Ig and is the main isotype in mucosae, where DC are numerous. We found that a functional FcαR (CD89) was expressed in situ and in vitro on interstitial-type DC but not on Langerhans cell-type DC. Interstitial-type DC expressed CD89 as a 50- to 75-kDa glycoprotein with a 32-kDa protein core, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 28 publications
7
89
2
1
Order By: Relevance
“…An additional property of IgA is its inability to trigger the release of inflammatory mediators through receptors specific for its Fc domain (42)(43)(44). In support of this are two reports showing differential pattern of in vitro-derived DC activation after surface binding of IgA as compared with other Ig isotypes (45,46). This is consistent with the multitask role of protecting against foreign substances and microbes, regulating the commensal microbiota, while at the same time not subjecting the mucosa to undue inflammation (47,48).…”
Section: Siga Biosynthesis and Function At Intestinal Mucosal Surfacessupporting
confidence: 74%
“…An additional property of IgA is its inability to trigger the release of inflammatory mediators through receptors specific for its Fc domain (42)(43)(44). In support of this are two reports showing differential pattern of in vitro-derived DC activation after surface binding of IgA as compared with other Ig isotypes (45,46). This is consistent with the multitask role of protecting against foreign substances and microbes, regulating the commensal microbiota, while at the same time not subjecting the mucosa to undue inflammation (47,48).…”
Section: Siga Biosynthesis and Function At Intestinal Mucosal Surfacessupporting
confidence: 74%
“…Like Fc␥R in mouse DCs, Fc␣R engagement in human DCs induces efficient maturation (33). By contrast, it was recently shown that human monocyte-derived DCs were not induced to mature after Fc␥R engagement (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The MR is a marker of alternatively activated cells with enhanced cell function, mediates both pinocytosis and phagocytosis, and serves as a molecular link between innate and adaptive immune response [26]. Because DC efficiently bind sIgA [7] via a receptor with lectin-like properties [25], we were interested to know whether NK cells may bind sIgA via MR. NK cells and monocytes did not bind anti-MR Ab, whereas the MR is highly expressed on monocyte-derived DC [29], as well as on monocyte-derived M ¶ [4]. Furthermore, the percentage of NK (CD3 -CD56 + ) cells binding sIgA did not change when L-fucose, D-galactose, D-glucose, D-mannose or N-acetyl-D-glucosamine were used as inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that DC express a receptor for IgA [7], and that the binding of IgA occurs via a mannose receptor (MR/CD206) which recognizes carbohydrates patterns [25]. Therefore, we asked whether NK cells constitutively express MR, which may mediate sIgA binding.…”
Section: Cd56mentioning
confidence: 99%
See 1 more Smart Citation